Obstacles to the realization of compact city strategy with emphasis on the central part of the city: Case study of central and ancient part of the city of Sary - mostafa ghadami; farveh Rahmani; jamaleddin Honarvar (تحقیقات کاربردی علوم جغرافیایی)
Industrial revolution and its resulting changes have led to urban horizontal growing. Environmental pollution, more energy consumption, development without planning, Increased spending on infrastructure, particularly in the area of urban construction are the consequences of the urban horizontal growing. To remedy the crisis, efforts have been made to recognize patterns of urban development and the realization of sustainable urban form. Meanwhile, the compact city strategy was presented to solve the proposed problems. Compact city is an urban strategy to tackle the problem of sporadic and uncontrolled physical growth of cities. This study aimed to identify the obstacles to the realization of compact city strategy in the central part of Sari. The research method is qualitative on the basis of a theoretical approach. Data was collected in two ways of documentation and semi-structured interviews. The sample included people involved in urban development projects. Purposeful sampling was done using the snowball technique and finally 10 specialists in the research area were selected as the study sample. Results suggest that the presence of monuments, low interest of investors for construction, and inefficient transport system were among the obstacles of the realization of compact city strategy in the research area